RELEVANCE OF RIGHT TO ECONOMIC SELF-DETERMINATION (RESD) PRINCIPLES OF INDONESIAN SOVEREIGNTY IN BILATERAL INVESTMENT TREATY (BIT) - Evi Kristhy, Mutia; Murhaini, H. Suriansyah (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
The RESD principle is relevant for protecting the sovereignty of the Indonesian state in BIT negotiations, formulations and implementation. This relevance is based on the willingness and ability of the Indonesian state to exercise its sovereign authority responsibly in managing foreign investment. Accountability of sovereignty functions in the context of foreign investment can be proven through the willingness and ability of the functions it carries to ensure the availability of political good and public good to all parties who invest in their jurisdiction. Proving the country can be done through three main principles of the implementation of state sovereignty, namely responsibly, in accordance with good governance, and international standards of civilization. These three principles are manifested in the country's willingness and ability to guarantee political good in carrying out foreign investment relations with foreign investors and partner countries. Political good in this context is democratic governance (rule of law), good governance (anti-corruption). The implication of this legitimacy is that the state is spared or even cannot be interfered by other authorities, because it has a bargaining position.Â Keywords: Right to Economic Self-Determination (RESD), Bilateral Investment Treaty (BIT), Sovereignty.